O processo de inserção de bebês em uma escola municipal de educação infantil de Belo Horizonte - Virgínia Souza Oliveira (2019)
In order to analyze how did happen the insertion process of twelve babies, aged between 06 and 18 months, at a municipal school of early childhood education in Belo Horizonte (EMEI-TUPI), we have utilized Ethnography of education as main theoretical methodological approach. Therefore, we have worked in field during the entire year of 2017; we have recorded in video the nursery’s routine, we have took field notes and we have made semi-structured interviews with the babies’ family members, teachers and pedagogy team. The Ethnographic perspective, in dialogue with Historical-Cultural Psychology and the Network of meanings theory, enabled us to comprehend the baby as person and his developmental process without fragmenting him. Their processes of insertion were influenced: (1) by their first two days at school; (2) by the exploring of new material, historical and cultural context; (3) by transformation processes of crying; (4) by the changing of sleep patterns; (5) by the getting sick processes and finally (6) by the babies’ meetings. We have verified that the babies changed and were changed by the context in which they were being inserted. Our investigations have also revealed that the babies’ biological rhythms have been gradually shaped by the institutional routine. Lastly, we have concluded that a network of meanings permeates the babies’ insertion processes, which are not linear and do not happen in the same way for all babies.